Pengaruh Total Asset Turnover, Return on Assets, Debt to Equity Ratio, Stock Return, dan Firm Size terhadap Firm Value - Destiana, Khalila Salma; Nyale, M Hendri Yan (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study evaluates the impact of TATO, ROA, DER, stock returns, and firm size on company value (PBV) for 28 infrastructure companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. The background to this research is the crucial role of the infrastructure sector amid government budget dynamics that affect corporate performance and investor perception. The results show that ROA, DER, and stock returns have a significant positive effect on company value. This indicates that high profitability, optimal debt management, and good stock returns send positive signals to the market. Conversely, TATO was found to have a significant negative effect, reflecting that inefficiencies in asset management can reduce investor confidence. Meanwhile, firm size had no significant impact on company value. This study recommends that investors use ROA, DER, and stock return as key indicators in decision-making. At the same time, companies are advised to optimise profitability and debt management to enhance their value in the eyes of investors.